2001
DOI: 10.1159/000054898
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Dopamine, Serotonin, and Norepinephrine Transporter Genes and Their Relationship to Temperamental Dimensions Measured by the Temperament and Character Inventory in Healthy Volunteers

Abstract: There is evidence for an association between polymorphisms of monoamine transporter genes and temperamental personality traits. Recent findings have shown that interaction of allelic variants of the different genes may contribute to the personality factors. We studied the association between temperamental personality dimensions measured with the Temperament and Character Inventory (TCI) and polymorphisms of the dopamine (DAT), norepinephrine (NET) and serotonin (5-HTT) transporter genes in 127 healthy Polish v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 30 publications
3
42
2
Order By: Relevance
“…Gelertner et al (1998) reported that Caucasians with the 5-HTTLPR s allele had higher scores on neuroticism compared to those with the l/l genotype, whereas the opposite pattern of findings was reported for African Americans. Results from samples of Polish (Samochowiec et al 2001) and Japanese individuals (Katsuragi et al 1999) suggest that the 5-HTTLPR s allele is associated with higher scores on harm avoidance. Conversely, no association was found in Finnish (Mazzanti et al 1998), Israeli (Ebstein et al 1997), and Japanese (Nakamura et al 1997) samples.…”
Section: Introductionmentioning
confidence: 97%
“…Gelertner et al (1998) reported that Caucasians with the 5-HTTLPR s allele had higher scores on neuroticism compared to those with the l/l genotype, whereas the opposite pattern of findings was reported for African Americans. Results from samples of Polish (Samochowiec et al 2001) and Japanese individuals (Katsuragi et al 1999) suggest that the 5-HTTLPR s allele is associated with higher scores on harm avoidance. Conversely, no association was found in Finnish (Mazzanti et al 1998), Israeli (Ebstein et al 1997), and Japanese (Nakamura et al 1997) samples.…”
Section: Introductionmentioning
confidence: 97%
“…An exonic RFLP in the norepinephrine transporter (NET) was examined in a sample of healthy subjects, but no associations were obtained with any of the TCI temperament scales or subscales. 69 Polymorphisms in the a1a adrenoceptor (ADRA1A) and a2a adrenoceptor (ADRA2A) genes did not show association with the TPQ dimensions in Chinese subjects. 103 Another study focusing on ADRA2A did find some associations of a common SNP in ADRA2A with measures of irritability, hostility and impulsivity.…”
Section: Noradrenalinementioning
confidence: 83%
“…68 In a more recent study using the TCI, DAT1 only showed association with the RD4 subscale measuring dependence vs independence. 69 In a study using extremely high-and low-scoring individuals, association was reported between DAT1 and NS. 41 After stratification for gender, the effect was only found in female subjects.…”
Section: Dopaminementioning
confidence: 98%
See 1 more Smart Citation
“…Individuals with greater novelty-seeking personality are often described as exploratory, curious, inquisitive, and enthusiastic (Kose, 2003). Strong evidence emerged from existing studies that the polymorphisms in DRD4, DRD2 and 5-HTTLPR were not connected to novelty-seeking personality (Burt, McGue, Iacono, Comings, & MacMurray, 2002;de Brettes et al, 1998;Ebstein, 2006;Ebstein et al, 1997;Hill, Zezza, Wipprecht, Locke, & Neiswanger, 1999;Kluger, Siegfried, & Ebstein, 2002;Kreek, Nielsen, Butelman, & LaForge, 2005; S. H. Lee, Ham, Cho, Lee, & Shim, 2007;Light et al, 2007;Munafò et al, 2003;Ricketts et al, 1998;Samochowiec et al, 2001;Schinka, Letsch, & Crawford, 2002;Suzuki et al, 2008;Tsuchimine et al, 2012;Van Gestel et al, 2002). In contrast, studies on COMT polymorphism revealed mixed and conflicting results (Calati et al, 2011;Demetrovics et al, 2010;Golimbet, Alfimova, Gritsenko, & Ebstein, 2007;Hashimoto et al, 2007;Hosák, Libiger, Cizek, Beránek, & Cermáková, 2006;Hoth et al, 2006;Kim, Kim, Kim, Lee, & Kim, 2006;Lichtenberg, Bachner-Melman, Ebstein, & Crawford, 2004;Light et al, 2007;Reuter & Hennig, 2005; S.-J.…”
Section: Novelty-seekingmentioning
confidence: 99%